CATALOGUE OF ASTROMETRIC POSITIONS OF JUPITER`S OUTER SATELLITES ON PHOTOGRAPHIC OBSERVATIONS IN MAO NAS OF UKRAINE IN 1987-1993 - Yizhakevych, O.; Andruk, V.; Pakuliak, L. (Одеські астрономічні публікації, 2017)
The catalog of 33 topocentric positions of Jupiter’s moons J6, J7, J8 has been created on photographic observations made in MAO NASU in 1987-1993. Positions are referred to the system of TYCHO-2 using the program package INUX/MIDAS/ROMAFOT. The comparison of observed positions was made online with their theoretical data of IMCCE (www.imcce.fr/sat).